2008
DOI: 10.1021/jp802086z
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Reactions between Acetylene Radical Cation and Water. Energies, Structures and Formation Mechanism of C 2H 3O + and C 2H 4O +• Ions

Abstract: Reactions of the acetylene radical cation (C2H2(+*)) with H2O were investigated using ion mobility mass spectrometry. The primary products are the C2H3O(+) and C2H4O(+*) ions, produced with an overall rate coefficient k(300 K) = 2(+/-0.6) x 10(-11) cm(3) s(-1) that increases with decreasing temperature. The C2H4O(+*) (adduct) vs C2H3O(+) (H loss) ratio also increases with decreasing temperature, and with increasing third-body pressure. Ab initio calculations on the products showed seven stable C2H3O(+) isomers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 43 publications
0
19
0
1
Order By: Relevance
“…Because previous mass spectrometry found acetyl from other precursors, 2, [47][48][49][50][51] we investigated its production from acetone. Previous reaction studies had suggested that acetone produces more than one ion structure at this mass.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because previous mass spectrometry found acetyl from other precursors, 2, [47][48][49][50][51] we investigated its production from acetone. Previous reaction studies had suggested that acetone produces more than one ion structure at this mass.…”
Section: Resultsmentioning
confidence: 99%
“…1, 2, [47][48][49][50][51] Ion/molecule reactions, collisional dissociation, and computational studies indicate that the acetyl cation (CH 3 CO + ) is the most stable structure, with less-stable configurations identified for protonated ketene (CH 2 COH + ) and the oxiranyl cation (H 2 COCH + ). The infrared spectrum and crystal structure of the acetyl cation have been measured previously in superacid matrices, [52][53][54] but no spectroscopy has been reported for other isomers.…”
Section: Introductionmentioning
confidence: 99%
“…11 Hydration of the acetylene radical cation (C 2 H 2 •+ ) results in the formation of the covalent ions C 2 H 3 O + and C 2 H 4 O •+ produced with an overall rate coefficient that increases with decreasing temperature. 12 The reactivity, combined with energetics, suggest that the C 2 H 4 O •+ adduct is vinyl alcohol (H 2 CCHOH •+ ), while the protonated ketene CH 2 COH + is the most likely observed C 2 H 3 O + ion. 12 The measured hydration energy can confirm the covalent nature of the ions as in the case of the acetylene trimer ion (C 2 H 2 ) 3 •+ where its sequential hydration energies with 1−6 water molecules are found to be identical to those of the benzene ion, thus confirming the formation of benzene cations in ionized acetylene clusters.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12 The reactivity, combined with energetics, suggest that the C 2 H 4 O •+ adduct is vinyl alcohol (H 2 CCHOH •+ ), while the protonated ketene CH 2 COH + is the most likely observed C 2 H 3 O + ion. 12 The measured hydration energy can confirm the covalent nature of the ions as in the case of the acetylene trimer ion (C 2 H 2 ) 3 •+ where its sequential hydration energies with 1−6 water molecules are found to be identical to those of the benzene ion, thus confirming the formation of benzene cations in ionized acetylene clusters. 13,17 Similarly, the measured hydration energy combined with structural calculations of the acetylene dimer ion (C 4 H 4…”
Section: ■ Introductionmentioning
confidence: 99%
“…Geburtstag gewidmet Epoxide I (Oxirane) sind wichtige Bausteine der Synthesechemie, insbesondere der Naturstoff-und Polymerchemie. [1,2] Oxiraniumkationen II sind bislang, trotz vieler experimenteller [3][4][5][6] und theoretischer Untersuchungen, [7][8][9] schwer fassbare reaktive Intermediate säurekatalysierter Epoxidöff-nungsreaktionen geblieben. Im Unterschied dazu könnte [15] die Protonierung von s 3 l 3 -Oxaphosphiranen [10][11][12][13][14] bisher unbekannte P-protonierte Oxaphosphiraniumderivate III liefern.…”
unclassified